REALIST ACTING APPROACH USING STANISLAVSKI CONSTANTIN ACTING METHOD IN EXTRACURRICULAR THEATER IN MAN 1 PALEMBANG - Cindyana Primeisela; Dessy Wardiah; Hasan Hasan (Pascasarjana Institut Seni Indonesia Padang Panjang, 2021)
The purpose of this study was to identify and describe the approach of realist acting with Konstantin Stanislavski's acting method. In this study conducted at MAN 1 Palembang with the number of students who actively participate in extracurricular theater, this study uses a qualitative research method with a descriptive approach. The data collection technique in this research is by observing, documenting, interviewing data to the supervisor and students. This study examines whether the theater extracurricular has applied a realist acting approach with Konstantin Stanislavski's acting method. The results of this study after observing this extracurricular application quite well with a realist acting approach with Konstantin Stanislavski's acting method, can be seen when students carry out the role training process seriously. into the roles they play.Keywords: Stanislavski's Acting Method; Theater Extracurricular; Realist Approach to ActingAbstrak Tujuan dari penelitian ini adalah untuk mengidentifikasi dan mendeskripsikan pendekatan akting realis dengan metode akting Konstantin Stanislavski. Penelitian ini dilakukan di MAN 1 Palembang dengan sejumlah siswa yang aktif mengikuti ekstrakurikuler teater. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data dalam penelitian ini adalah dengan mengamati, mendokumentasikan, serta mewawancarai dosen pembimbing dan mahasiswa. Penelitian ini mengkaji apakah ekstrakurikuler teater telah menerapkan pendekatan akting realis dengan metode akting Konstantin Stanislavski. Hasil penelitian menunjukkan bahwa penerapan ekstrakurikuler ini cukup baik dengan pendekatan akting realis dengan metode akting Konstantin Stanislavski, dapat dilihat ketika siswa melaksanakan proses pelatihan peran dengan sungguh-sungguh ke dalam peran yang mereka mainkan.Kata Kunci: Metode Akting Stanislavski; Ekstrakurikuler Teater; Pendekatan Realis untuk Akting